2018
DOI: 10.3844/jcssp.2018.1588.1598
|View full text |Cite
|
Sign up to set email alerts
|

The Extent of Smartphones Users to Adopt the Use of Cloud Storage

Abstract: Recently, technology has witnessed a rapid progress and dominates all aspects of life systematically. Smartphones are devices that users can depend on managing and storing data. Moreover, they are used to save, update and secure the private information of users by using Cloud Storage such as iCloud, Dropbox and Google Drive. This study presents and adjusts the Technology Acceptance Model (TAM) specifically, perceived ease of use, usefulness, attitude toward usage and behavioral intention. Additionally, the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 37 publications
(41 reference statements)
0
12
0
Order By: Relevance
“…As observed in the figures, it noticed that in blockchain the information does not keep at a central point like the conventional security methods (Hasan and Alhayani 2021;Yahya et al 2021; Abu-Rumman 2021; Abu-Rumman et al 2021). The multiple copies of similar data are stored in various locations and on various devices, and hence it is called distributed technology (Aldiabat et al 2018(Aldiabat et al , 2019. As the multiple copies of the same data available, the loss of any single point of storage does not affect the security of the original data (Rashid et al 2021;Chen et al 2019).…”
Section: Emergence Of Blockchainmentioning
confidence: 99%
See 1 more Smart Citation
“…As observed in the figures, it noticed that in blockchain the information does not keep at a central point like the conventional security methods (Hasan and Alhayani 2021;Yahya et al 2021; Abu-Rumman 2021; Abu-Rumman et al 2021). The multiple copies of similar data are stored in various locations and on various devices, and hence it is called distributed technology (Aldiabat et al 2018(Aldiabat et al , 2019. As the multiple copies of the same data available, the loss of any single point of storage does not affect the security of the original data (Rashid et al 2021;Chen et al 2019).…”
Section: Emergence Of Blockchainmentioning
confidence: 99%
“…Some other recent works (Yahya et al 2021;Abu-Rumman 2021;Abu-Rumman et al 2021;Aldiabat et al 2018Aldiabat et al , 2019Rashid et al 2021;Chen et al 2019;Wang et al 2018;Zhao et al 2018;Zhang et al 2018a) reported those are based on blockchain for the medical data storage and sharing in the cloud computing environment. The blockchain-based data-sharing framework proposed in Yahya et al (2021) that adequately approaches the access control difficulties connected with sensible medical data collected in the cloud employing built-in and immutability independence features of the blockchain.…”
Section: Block Chain-based Healthcare Systemsmentioning
confidence: 99%
“…Youssef et al ( 2017 ) have proposed new resource distribution methods that permit the coupling of NOMA with MIMO frameworks (Aldiabat et al 2018 , 2019 ). As in most downlink NOMA frameworks, the relative decency (PF) scheduler is utilized.…”
Section: Standards Of Future Wireless Communicationsmentioning
confidence: 99%
“…As the BS and RU have multiple reception apparatuses, thusly they think about (1) beamforming and (2) arbitrary receiving wire choice methodologies at the BS and RU. Youssef et al (2017) have proposed new resource distribution methods that permit the coupling of NOMA with MIMO frameworks (Aldiabat et al 2018(Aldiabat et al , 2019. As in most downlink NOMA frameworks, the relative decency (PF) scheduler is utilized.…”
Section: Integration Of Massive Mimomentioning
confidence: 99%
“…In addition, genome sequencing could be used to study the virulence and pathogenicity of the virus, as well as the evolutionary linkages between hosts and viruses (Shaibu et al 2021 ). SARS-CoV-2 is rapidly spreading through countries, and there has been considerable concern about whether the spread is due to mutations in the virus (Aldiabat et al 2018 ; Alhayani and llhan 2021 ).…”
Section: Introductionmentioning
confidence: 99%